EDUKASI DETEKSI DINI KANKER LEHER RAHIM PADA WANITA USIA SUBUR DI KELURAHAN SAMAPUIN KABUPATEN SUMBAWA - Luh Putu Sri Yuliastuti; Gladeva Yugi Antari (Jurnal Pengabdian Ilmu Kesehatan, 2022)
Cancer of the cervix or cervix is ​​the second most common cancer in women living in less developed areas. Prevention that can be done for cervical cancer include delaying sexual activity, using barrier contraception, using the HPV vaccine and screening/early detection. The purpose of this activity is to provide insight to women of childbearing age about early detection of cervical cancer in Samapuin Village, Sumbawa Regency. This service activity plan is carried out with lectures and discussions. This activity was carried out for 1 day on May 20, 2022. The participants of the activity were 10 women of childbearing age located in Samapuin Village, Sumbawa Regency. The achievement of the material in general is good, seen from the evaluations carried out on the participants. So it can be concluded that the purpose of this service activity has been achieved.